The pattern of soil water extraction by individual kiwifruit vines : a thesis presented in partial fulfillment of the requirements for the Master of Agricultural Science in Soil Science at Massey University - Snow, Valerie Olga (Massey University, 1987)
In order to efficiently design and operate irrigation systems water balance studies are needed. To date few of these studies have been carried out on kiwifruit. Detailed measurements of water extraction were made beneath two 7 year old kiwifruit vines. Under-vine covers were used on these vines to exclude rainfall and irrigation. Measurements of fruit size and leaf water potential were made on the two covered vines and on adjacent irrigated vines. In addition, solar radiation and air temperature were monitored in the orchard block. In concurrent studies, the root distribution of vines in the orchard were determined and heat pulse measurements of sapflow were made. The water extraction pattern showed little variation with depth to the maximum depth of measurement (2.2 m). There was, however, considerable variation in extraction with horizontal distance away from the vine. This variation may be explained in terms of the root distribution. The soil volume may be divided into the zone of occupation, in which the soil is completely occupied by the plant roots, and the zone of exploration, which is the volume of soil in which there are a few roots but the soil is still largely unexplored. Within the zone of occupation, water is uniformly extracted despite variation in root density. Water appears to be extracted from the zone of exploration primarily by flow of water towards the zone of occupation, where the soil water potential is lower. The fruit volume and leaf water potential measurements were used to indicate the onset of water-stress. At this time, soil water potential in the zone of occupation was between -40 and -50 kPa. The size of the reservoir of readily availible water was found to be at least 2.1 m 3 for 7 year old vines, and is projected to rise to a maximum of at least 6.5 m3 in three or so years in this orchard. Whereas the vine canopy may, by management, mature in 3 years, the root system may take 10 years to mature, so irrigation requirements of young vines will be higher than for mature vines. This is contrary to common assumptions made in standard methods for designing horticultural irrigation systems and is due to changes in the size of the reservoir rather than changes in the rate of water use. When there is radial variation in water extraction it is important to take account of the variation when calculating volumes of water extracted from the soil. The rate of water use by the vines, as estimated by the water balance method and the heat pulse technique, was found to be considerably lower than that predicted by the equilibrium evapotranspiration rate. This may be due to experimental error, and further work is required to clarify this matter.
Keywords: Kiwifruit; Plants -- Absorption of water